Win-win: designing dual-use in climate projects for effective anti-corruption in Bangladesh. (26th November 2022) - Khan, Mushtaq; Watkins, Mitchell; Aminuzzaman, Salahuddin; Khair, Sumaiya; Khan, Muhammad Zakir Hossain
ABSTRACT: Climate adaptation projects in Bangladesh have been widely affected by high levels of corruption and resource leakage. However, the dual-use characteristics of climate adaptation investments create incentives for influential households to monitor projects in their own interest. We theorize that these households can effectively use informal power and networks to constrain corruption by contractors and officials. Increasing the level of dual-use benefits is therefore a viable way of reducing corruption in contexts of poor governance. We test this hypothesis using data from a survey of 1, 901 households living near four recently completed climate projects and interviews with over 30 key informants. The results indicate that households are more likely to monitor climate projects if they provide dual-use benefits and households with above-average incomes from agricultural and business activities are the most likely to benefit from dual-use attributes. Furthermore, we find that higher levels of monitoring by these influential households are associated with reduced corruption during project implementation.